2011
DOI: 10.1021/jp110037g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Effects on Rotational Correlation Times of Tris(β-diketonato)aluminum(III) in CO2 by 27Al NMR Relaxation Measurements

Abstract: (27)Al NMR longitudinal relaxation times, T(1,obs)((27)Al), of [Al(acac)(3)] and [Al(hfa)(3)] (Hacac = acetylacetone, Hhfa = hexafluoroacetylacetone) in CH(3)CN and CO(2) were measured over a wide range of temperature and pressure. The rotational correlation times, τ(r), of the tris(β-diketonato)aluminum(III) complexes were determined from T(1,obs)((27)Al) using (27)Al quadrupole coupling constants, eQq/h((27)Al), which were also obtained to be 3.11 and 3.22 MHz for [Al(acac)(3)] and [Al(hfa)(3)], respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The octahedral environment is substantially distorted from ideal parameters in all three compounds, with cis and trans angles varying from 74.1(3)°to 98.64 (10) of the coordination geometry, the value τ, which measures how closely a distorted five-coordinate compound approximates either a trigonal bipyramidal or square pyramidal geometry, was calculated according to the reported method. 74 The value of τ = 0.82 suggested that the geometry around the aluminum centers is best described as distorted trigonal bipyramidal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The octahedral environment is substantially distorted from ideal parameters in all three compounds, with cis and trans angles varying from 74.1(3)°to 98.64 (10) of the coordination geometry, the value τ, which measures how closely a distorted five-coordinate compound approximates either a trigonal bipyramidal or square pyramidal geometry, was calculated according to the reported method. 74 The value of τ = 0.82 suggested that the geometry around the aluminum centers is best described as distorted trigonal bipyramidal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With continuing research interest and increasing technological importance of nanomaterials, particularly thin films of functional materials, the quest for new metal–organic compounds, enabling a controlled synthesis of new materials has gained significant impetus in recent years. Aluminum compounds supported by monoanionic alkoxide and β-diketonate ligands are well-known and extensively investigated. Among halide and alkyl aluminum complexes, they are the most widely used precursor classes for chemical vapor depositions of Al 2 O 3 despite the drawbacks of being prone to hydrolyses or showing low volatilities. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study already mentioned in section 3.2, Umecky and co-workers 199 presented measurements of 27 Al (I = 5/2) and 13 C relaxation in tris(acetylacetonato)aluminium(III) and its analogue with the methyls replaced by CF 3 groups, dissolved in supercritical carbon dioxide. The 27 Al T 1 -values were obtained over a range of temperatures and pressures and the dependences of the rotational correlation time on viscosity and density was investigated.…”
Section: Nuclear Spin Relaxation In Gasesmentioning
confidence: 99%